ANALISIS POTENSI BEBAN EMISI PADA PEMBANGKIT LISTRIK TENAGA UAP (PLTU) CO-FIRING DAN KEMAMPUAN SERAPAN TANAMAN PENGHIJAUAN DI AREA KERJA TERHADAP EMISI CO2 PT MAKMUR SEJAHTERA WISESA KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN - Joko Agus Pamuji Wibowo; Suyanto Suyanto; Gusti Rusmayadi; Abdul Ghofur (EnviroScienteae, 2023)
One of the policies of the Ministry of Energy and Mineral Resources of the Republic of Indonesia related to the contribution in reducing the effect of greenhouse gases is to terminate or discontinue the construction permit for coal-fired Steam Power Plants, which will begin gradually in 2025. This policy is considered difficult to implement, because there are still many Coal Power Plant that are still operating in accordance with the permits issued by the Government. So in addition to the policy of retiring coal-fired power plants, the Government has implemented a policy of Co-firing Power Plant innovation for better environmental management and supporting sustainable development goals. Coal Power Plant PT Makmur Sejahtera Wisesa (MSW) in South Kalimantan will implement the Power Plant Co-Firing policy. This study aims to analyze the amount of power plant greenhouse gas emissions so far, then project the amount of emissions until 2030 with the treatment of coal-fired power plants and co-firing power plants, and calculate the carbon uptake of plants in reforestation areas at PT MSW Power Plant. The method used is the data collection and calculation of Green House Gas Emissions (GHG) produced so far and then simulated calculations using waste pellets as co-firing fuel, using the 2006 Intergovernmental Panel on Climate Change (IPCC) Guidelines approach method. The calculation results The GHG emission is projected until 2030 using the Auto- Regressive Moving Average (ARIMA) method. The GHG emissions produced by the Power Plant are compared with the company's efforts so far by planting trees in the reforestation area of the PLTU. To assess these efforts, an evaluation of the GHG emissions produced by the ability of reforestation plants to absorb CO2 emissions has been carried out so far. The results of the study obtained that the GHG Emissions of the PT MSW Power Plant in 2021 amounted to 156,436 tons / year. From the results of data projections obtained for the next 9 years (until 2030) the results of gas emissions will decrease every year. Theresults of the inventory and estimation of the absorption capacity of plants in the reforestation area of PT MSW Power Plant with an area of 30,535.12 m², is 3,820.5 tons/year and carbon absorbed is 103.86 tons. With a total number of tree plants, an inventory of 2,764 trees was carried out.